Regional Economic Integration of Bosnia and Herzegovina – Obstacles for (Re)integration - Grbo, Zinka (LeXonomica, 2021)
Discussions: Regional Economic Integration of Bosnia and Herzegovina – Obstacles for (Re)integration Razprave: Regionalna ekonomska integracija Bosne in Hercegovine - ovire in (re)integracija